E-mail load, workload stress and desired e-mail load: a cybernetic approach - Jean-Francois Stich; Monideepa Tarafdar; Patrick Stacey; Cary L. Cooper (2018)
Purpose Using e-mail is a time-consuming activity that can increase workload stress. The purpose of this paper is to investigate the relationship between the individual’s e-mail load, workload stress and desired e-mail load, drawing from the cybernetic theory of stress. Design/methodology/approach Based on prior theory, the authors first hypothesized relationships among e-mail load, workplace stress and desired e-mail load. The authors then tested these relationships on a sample of 504 full-time workers in the USA, using survey data and covariance-based structural equation modeling techniques. Findings The authors find that higher e-mail load is associated with higher workload stress; higher workload stress is associated with lower desired e-mail load; lower desired e-mail load is associated with lower e-mail load; and higher workload stress is associated with higher psychological strain, higher negative emotions and lower organizational commitment. Originality/value The study provides a novel understanding of workload stress due to e-mail load, through the lens of cybernetic theory. It contributes to the e-mail overload and technostress literatures by conceptualizing desired e-mail load as a potential outcome of workplace stress and as a regulator for e-mail load. For practitioners, the study highlights the importance of managing employees’ e-mail load to prevent the negative effects of workplace stress and associated strains.